PENERAPAN METODE VECTOR AUTO REGRESSION DALAM INTERAKSI KEBIJAKAN FISKAL DAN MONETER DI INDONESIA - Sutawijaya, Adrian; Lestari, Etty Puji (Universitas Muhammdaiyah Surakarta, 2013)
The purpose of this study is to analyze the interaction of fiscal and monetary policy in Indonesia, especially after the introduction of fiscal and monetary policy shocks. The research method used is the vector autoregression (VAR). VAR is usually used for projecting coherent system variables and time to analyze the dynamic impact of disturbance factors contained in the system variables. Variables used in this study is the level of interest rates as a proxy for monetary policy instruments, government expenditures as a proxy for fiscal policy, inflation rates and national income. The results show that fiscal policy is a negative shock to inflation and responded with a tight monetary policy, while the shock in monetary policy will reduce national income. The application of fiscal and monetary policies that will effectively promote economic growth.